Changes in smoking cessation assistance in the European Union between 2012 and 2017: pharmacotherapy versus counselling versus e-cigarettes. Issue 1 (21st March 2018) - Filippidis, Filippos T; Laverty, Anthony A; Mons, Ute; Jimenez-Ruiz, Carlos; Vardavas, Constantine I
Abstract : Background: The landscape of smoking cessation may have changed in Europe recently. Objectives: To identify changes in use of smoking cessation assistance in the European Union (EU) and factors associated with use of cessation assistance. Methods: Data from the 2012 (n=9921) and 2017 (n=9489) waves of the Eurobarometer survey were used. Self-reported use of smoking cessation assistance was assessed among smokers who had ever tried to quit and former smokers. Changes in use of each type of assistance were assessed using logistic regression. Results: Among current and former smokers, those who had ever attempted to quit without assistance increased from 70.3% (2012) to 74.8% (2017). Current smokers were more likely to have used any assistance compared with former smokers (P<0.001). Use of e-cigarettes for smoking cessation assistance increased (3.7% to 9.7%)%), while use of pharmacotherapy (14.6% to 11.1%)%) and smoking cessation services (7.5% to 5.0%)%) declined. Younger people were more likely to have reported e-cigarette use for smoking cessation but less likely to have used a cessation service. Individuals living in countries with comprehensive smoking cessation policies were more likely to have used any cessation assistance (adjusted OR (aOR)=1.78; 95% CI 1.15 to 2.76), pharmacotherapy (aOR=3.44; 95% CI 1.78 to 6.66) and smoking cessation services (aOR=2.27; 95% CI 1.27 to 4.06) compared with those living in countries with weak smoking cessation policies. Conclusions: These findings highlight the need for approaches that ensure that smokers get support to quit smoking across the EU. The question of whether the availability of e-cigarettes will displace other methods, and the impact of such a displacement, should be closely evaluated.